The Histopathological Features of Syphilis and Its Mimickers - Purnamasari, Indah; Hidayati, Afif Nurul; Kusumastuti, Etty Hary; Effendy, Isaak (Folia Medica Indonesiana, 2023)
Highlights: • The importance of having a strong suspicion for syphilis and maintaining close contact between dermatologists and pathologists cannot be understated. • Understanding the clinical relationship and histopathological features of syphilis is crucial for accurate diagnosis and distinction from its histopathologic mimickers. Abstract: Settings Syphilis, also known as